2004
DOI: 10.1021/jm049706k
|View full text |Cite
|
Sign up to set email alerts
|

Rational Design, Synthesis, and Biological Evaluation of Bis(pyrimido[5,6,1-de]acridines) and Bis(pyrazolo[3,4,5-kl]acridine-5-carboxamides) as New Anticancer Agents

Abstract: The good results obtained with pyrimido[5,6,1-de]acridines 7 and with pyrazolo[3,4,5-kl]acridinecarboxamides 8 prompted us to the synthesis of two new series of bis acridine derivatives: the bis(pyrimidoacridines) 5 and the bis(pyrazoloacridinecarboxamides) 6. Compounds 5 can be regarded also as cyclized derivatives of bis(acridine-4-carboxamides) 3 and compounds 6 as cyclized derivatives of bis(acridine-4-carboxamides) 4. The noncovalent DNA-binding properties of these compounds have been examined using fluor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 21 publications
0
33
0
Order By: Relevance
“…Furthermore, the shortest linker gives rise to a lower cytotoxicity and DNA affinity with respect to the longest linker. These results are valid when the acridine possesses a fused pyrazole or pyrimido ring [71]. Furthermore, Wakelin [72] completed the study with semirigid chains (piperazine) as the linker and a morpholino unit in the carboxamide.…”
Section: Acridine Compoundsmentioning
confidence: 80%
See 1 more Smart Citation
“…Furthermore, the shortest linker gives rise to a lower cytotoxicity and DNA affinity with respect to the longest linker. These results are valid when the acridine possesses a fused pyrazole or pyrimido ring [71]. Furthermore, Wakelin [72] completed the study with semirigid chains (piperazine) as the linker and a morpholino unit in the carboxamide.…”
Section: Acridine Compoundsmentioning
confidence: 80%
“…8 [70][71][72] studied related structures and confirmed that the bisacridone derivatives are more active than the corresponding monomers. Furthermore, the shortest linker gives rise to a lower cytotoxicity and DNA affinity with respect to the longest linker.…”
Section: Acridine Compoundsmentioning
confidence: 83%
“…The hollow fiber assay has been incorporated into the drug discovery programs of many laboratories around the world including Argentina,69 Austria,70 France,71 Germany,72 India,73Italy,7478 New Zealand,79 Poland,80,81 Spain,82,83 Sweden,84 and the United Kingdom 8589…”
Section: Discussionmentioning
confidence: 99%
“…The most active compounds identified from this study resulted in highly cytotoxic molecules that exhibited IC 50 values against HT-29 cells at low or subnanomolar concentrations ( 17 , 18a , and 18b ). Second generation ‘cyclized’ acridone carboxamides ( 19 , 20a , and 20b ) were generally poorer DNA binders than the corresponding ‘open’ analogues and possessed a preference for AT-rich sequences; however, they continued to maintain low to subnanomolar cytotoxic activity [68]. Preliminary in vivo results from a hollow fiber assay demonstrated that 19 exhibited in vivo activity worthy of further testing in xenograft models, which are currently underway.…”
Section: Synthetic Dimersmentioning
confidence: 99%